2019
DOI: 10.1177/1089268019857936
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Hurt: Revisiting the Relationship Between Social and Physical Pain

Abstract: Pain overlap theory has generated decades of controversy and still receives considerable research attention. A major advance has been the revelation that social and physical pain activate similar neural regions, providing suggestive evidence of a “piggybacked” alarm system that coevolved to detect social exclusion. Recent developments, however, have brought neural evidence for pain overlap into question. We analyze these developments from a social psychological perspective and identify the need for a reformula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 153 publications
1
18
0
Order By: Relevance
“…However, the direct overlap between neural processes implicated in physical and social pain is uncertain, and the association may reflect more fundamental motivational pathways. 15 While the associations between loneliness and later pain parallel previous research, 19 the longitudinal results for pain being related to later loneliness were more robust than those of other population studies. For example, analyses of the Health and Retirement study reported by Emerson et al 12 did not find that baseline pain predicted future loneliness, though the combination of pain both at baseline and follow-up was related to loneliness.…”
Section: A C C E P T E Dsupporting
confidence: 68%
See 2 more Smart Citations
“…However, the direct overlap between neural processes implicated in physical and social pain is uncertain, and the association may reflect more fundamental motivational pathways. 15 While the associations between loneliness and later pain parallel previous research, 19 the longitudinal results for pain being related to later loneliness were more robust than those of other population studies. For example, analyses of the Health and Retirement study reported by Emerson et al 12 did not find that baseline pain predicted future loneliness, though the combination of pain both at baseline and follow-up was related to loneliness.…”
Section: A C C E P T E Dsupporting
confidence: 68%
“…However, the direct overlap between neural processes implicated in physical and social pain is uncertain, and the association may reflect more fundamental motivational pathways. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, correctness rate did not significantly differ between the inclusion and exclusion groups. In recent years, studies have shown that social exclusion causes pain 27 , 28 . The neural regions that process the emotional components of pain include the ACC and the anterior insula; these regions exhibit greater activation in response to the experience of social exclusion 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Being ignored and excluded is an intensely painful experience ( DeWall et al, 2010 ; Eisenberger, 2012 ; Ferris et al, 2019 ) and strongly motivates its targets to achieve re-affiliation ( Williams, 2007 ). Ostracized individuals, thus, tend to try to connect with individual interaction partners ( Maner et al, 2007 ), are motivated to work with others, join social clubs ( Baumeister and Leary, 1995 ), or even join extreme groups ( Hales and Williams, 2018 ).…”
Section: Introductionmentioning
confidence: 99%